Molecular Study of Lysozyme Resistant Gram- negative Bacteria - Hussain Adnan Hashim (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Lysozyme, an essential antimicrobial enzyme found in bodily fluids, serves as a vital component of the innate immune system, acting primarily by hydrolyzing bacterial cell walls. Specific Background: While lysozyme effectively targets Gram-positive bacteria, Gram-negative bacteria often display resistance due to their protective outer membrane. Recent studies have suggested that specific genes, such as icaA and OatA, may contribute to lysozyme resistance by enhancing biofilm formation and altering cell wall structure. Knowledge Gap: Limited molecular data exist regarding the prevalence of these resistance genes among Gram-negative pathogens isolated from burn patients, particularly in Iraq. Aims: This study aimed to identify the presence of icaA and OatA genes in Gram-negative bacterial isolates from burn patients and assess their potential roles in lysozyme resistance. Results: Among 36 bacterial isolates, Pseudomonas aeruginosa (72.20%) and Klebsiella pneumoniae (27.80%) were dominant. The icaA gene was detected in 30.60% and the OatA gene in 22.20% of isolates. Novelty: This research provides the first molecular evidence of icaA and OatA gene distribution among lysozyme-resistant Gram-negative bacteria in burn patients in Thi-Qar. Implications: The findings highlight the need for continuous molecular surveillance of resistance determinants to improve antimicrobial strategies and infection control in burn treatment settings.Highlight : Lysozyme is a key natural antibacterial enzyme. icaA and OatA genes were found in burn bacterial isolates. Monitoring resistance genes is essential. Keywords : Pseudomonas Aeruginosa, OatA Gene, icaA Gene, Burn Patient, Lysozyme Resistant